The Berenstain Bears and Mama for mayor! - Berenstain, Jan; Berenstain, Mike 1951- (New York : Harper, 2012)
Make your way to the ballot box --- Mama is running for mayor! There are lots of improvements to be made in Bear Country, and Mama has a plan. She's going to fix the roads, pick up the trash, and replace the broken streetlights. But will she promise too much?
Keywords: Berenstain Bears (Fictitious characters); Families; Mayors; Berenstain Bears (Fictitious characters); Family life; Mayors